"Self-Referred" – A Physician's experience of referred ear pain as a symptom of pyogenic liver abscess, a case report. (November 2021) - Lockhart, Michael; Lockhart, Andrew; Barra, Eoghan de
Highlights: Secondary otalgia is a novel presenting symptom for pyogenic liver abscess. This could be explained as referred pain from irritation of the vagus nerve. The primary author of this case was also the patient. Abstract: Background: The presenting symptoms of liver abscess are typically non-specific, including pyrexia, right upper quadrant tenderness, nausea/vomiting and fatigue. We discuss a case of pyogenic liver abscess which presented with non-specific symptoms and severe left-sided ear pain. To our knowledge, this is a previously unreported presenting symptom of liver abscess in adulthood. This case is also somewhat unique in that the primary author is the patient in question. Case Report: A young male patient in his twenties, working as a junior doctor, presented with a seven-day history of intermittent pyrexia, fatigue, nausea, vomiting and severe left-sided ear pain. A CT abdomen/pelvis revealed a large liver abscess in the right hepatic lobe. A percutaneous drain was inserted with US guidance and the patient completed a prolonged course of antibiotics (14 weeks total) with CT-confirmed resolution of the abscess at that point. The left-sided ear pain resolved within hours of the percutaneous drain insertion. Conclusions: To our knowledge, this is the first reported case of a liver abscess in an adult patient presenting with severe left-sided ear pain. We propose that this pain was secondary otalgia due to vagus nerve irritation at the level of the liver abscess.